Tokoh Saridin dalam Pementasan Kethoprak Saridin Andum Waris: Representasi Kearifan Kritik Masyarakat Jawa Pesisir - Sukarjo Waluyo (Endogami: Jurnal Ilmiah Kajian Antropologi, 2020)
Several districts and cities in Central Java have begun to identify the richness of local history, art and culture to become regional icons. Pati Regency is currently starting to develop a discourse as "Kethoprak City". Meanwhile, the city of Solo - Solo is often referred to as the hometown of kethoprak - was previously known as the City of Tourism and Culture because it has various assets of Javanese history, culture and arts. Kethoprak Pati (kethoprak pesisiran) and kethoprak Solo and Jogja (kethoprak Mataraman), if we look closely, will find several differences, one of which can be seen from the tendency of the plays in the performance. Kethoprak Pati features many plays that tell the story of the north coast of Java (Coastal Java). Some of the plays that are often played include the character Saridin that we can see in many plays such as Saridin Born, Saridin Andum Waris, Geger Palembang, Ontran-ontran Cirebon, Bedhahing Ngerum, Ondorante, and Lulang Kebo Landoh. The people of Pati and its surroundings recognize Saridin as a strange person and likes to do whatever he wants. However, he is also known as a powerful person and often breaks through common logic to reveal truth and justice. The existence of Saridin in the speech stories and kethoprak performances is often seen as a representation of critical wisdom in the Javanese coastal community.